Improved Hip Flexibility and Gluteal Function Following a Daily Lunge-and-Reach Stretching Intervention - Brent A. Ehresman; B.J. Lehecka; Damien Hiser; Levi Koster; Jessica Wietharn (International Journal of Sports Physical Therapy)
# Background